Synthesis of two potential anticancer copper(ii) complex drugs: their crystal structure, human serum albumin/DNA binding and anticancer mechanism. (6th February 2017) - Hu, Kun; Li, Feiyan; Zhang, Zhong; Liang, Fupei
Abstract : Two potential anticancer copper(ii ) complex drugs showed better activity than cisplatin against HeLa cells, and efficiently bonded with DNA/HSA. Abstract : Two hydrazone ligands 8-quinolinecarbaldehyde 3-methoxybenzoylhydrazone (L1) and 8-quinolinecarbaldehyde benzoylhydrazone (L2) and the corresponding mononuclear copper(ii ) complexes [Cu(L1)(NO3 )2 ] (1 ) and [Cu(L2)(CH3 O)NO3 ] (2 ) have been synthesized. The structures of complexes1 and2 were characterized by X-ray crystallography, elemental analyses, FT-IR and HRMS (ESI). Efficient binding of the complexes (1 and2 ) and ligands (L1 and L2) with protein (human serum albumin, HSA) has been established by UV-vis, fluorescence, synchronous fluorescence spectroscopy, and molecular docking methods. Fluorescence spectra show that both complexes strongly interact with protein. And the Trp residue, the intrinsic fluorophore in HSA, was induced to a less hydrophobic microenvironment with the addition of test complexes. Meanwhile, the fluorescence quenching mechanism was determined to be static quenching. Interaction of the complexes (1 and2 ) and ligands (L1 and L2) with calf-thymus DNA (CT-DNA) has been investigated by UV-vis and fluorescence methods which showed that the compounds interacted with CT-DNA through intercalation. Moreover, the molecular docking study indicated that the complex is embedded into site I (subdomain IIA) of HSA. In addition, the complexes exhibited significant cytotoxicity against a human cervical cancer cell line (HeLa), and complexes1 and2 showed better activity than cisplatin. The complexes could cause HeLa cell cycle arrest at the G2 phase. And mitochondrial dysfunction was induced by both of the complexes.